Da luz da lamparina ao opaco refletor: Ituiutaba, Minas Gerais, 1950-1980 - Muniz, Ana Maria Alves (2014)
This dissertation is about a research held in Ituiutaba, a city in the Western of Minas Gerais, in Pontal do TriânguloMineiro region, commonly referred to as Pontal doTriângulo or simply Pontal. This is an approach that concerns to the big rice farms from the municipality, between the 1950s and 1980s, highlighting the processing of this cereal and on what this activity has influenced the city and its inhabitants. With the aim of stressing this agricultural phase, many documents were researched, public and private ones, virtual or not; among them, newspapers, literature, images, IBGE data, memorialists, and posture codes.The research even incorporates reports and the production of a documentary video about those people who had their lives immersed in this complex context. In this view, we captured in audio and video the social experiences of those who had some connection, or that worked with, this kind of production in Ituiutaba, considered at that first decade, the Rice Capital , title that doesn t define the place anymore.The term opaque reflector impliesa distance from a moment to other. The figure of the reflector appears as an object that transmits light generated by electricity, that is, it belongs more to nowadays than to the past. At the same time, the term opaque refers to how difficult it is to see the past. Therefore, the opacity is related to what we can hardly see.